1982
DOI: 10.1152/ajpregu.1982.242.5.r482
|View full text |Cite
|
Sign up to set email alerts
|

Renal function, heart rate, and blood pressure during exercise and avoidance in dogs

Abstract: The effects of two behavioral tasks, treadmill exercise and shock avoidance, on renal and cardiovascular function were examined in dogs during intravenous infusion of isotonic saline. Urine was collected with a bladder catheter. Control experiments established steady base lines of urine flow (V), sodium excretion (UNaV), glomerular filtration rate (GFR), free water clearance (CH2O), heart rate (HR), and arterial pressure (Pa). Exercise led to increased V, UNaV, GFR, HR, and Pa with no change in CH2O. Avoidance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…In the first study, 5 three of six conscious, saline-infused dogs decreased U Na V during SNS arousal, demonstrating individual differences in the response patterns as we found in our subjects. In a second study, 6 nine dogs increased and 21 dogs decreased U Na V during SNS arousal.…”
Section: Figure 2 Line Graphs Showing Patterns Of Plasma Renin Activsupporting
confidence: 71%
“…In the first study, 5 three of six conscious, saline-infused dogs decreased U Na V during SNS arousal, demonstrating individual differences in the response patterns as we found in our subjects. In a second study, 6 nine dogs increased and 21 dogs decreased U Na V during SNS arousal.…”
Section: Figure 2 Line Graphs Showing Patterns Of Plasma Renin Activsupporting
confidence: 71%
“…Previous studies of avoidance conditioning have reported acute decreases in renal blood flow, 22 decreases in renal excretion of sodium and water, 12 and increases in plasma renin activity." In the present experiments, avoidance sessions consumed only 90 minutes of the 24-hour day.…”
Section: Discussionmentioning
confidence: 98%
“…Abnormal retention of sodium may contribute to hypertension in other ways as well (3). Studies in the dog (4) and rat (5) show that psychological stress reduces renal excretion of sodium and fluid. This stress-induced retention is greater among young spontaneously hypertensive rats than among rats with no genetic predisposition for hypertension (5).…”
Section: Psychological Stress Induces Sodium and Fluid Retention In Mmentioning
confidence: 99%
“…Reports that stressful mental tasks increase plasma renin activity and decrease renal blood flow in certain individuals, particularly those with one or two hypertensive parents and those showing high heart rate responses to stress, suggest but do not demonstrate that excretion of sodium and fluid may be reduced (6)(7)(8). High heart rate response in humans reflects enhanced sympathetic nervous system activity during competitive and other mental tasks (7); in animals, stressinduced sodium retention is sympathetically mediated (4,5). The purpose of the present study was to determine whether exposing young men to competitive mental stress reduces their excretion of sodium and fluid, and whether any observed reductions are greater among those with known risk factors for hypertension [for example, parental or borderline hypertension (9, 10)] or those demonstrating high heart rate responses to stress.…”
Section: Psychological Stress Induces Sodium and Fluid Retention In Mmentioning
confidence: 99%